Pengaruh Bentuk Umpan Pancing Buatan (Jigs) Terhadap Pola Aliran Fluida - Eko Setyo Adi Santoso; Ikhwanul Qiram; Anas Mukhtar (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2020)
Jig is a fishing rod that is usually used to catch squid or cuttlefish in the form of fish, shrimp, or others. This study aims to determine the effect of differences in the shape of the surface of the jig on the flow pattern of freshwater fluids. The study used a variation of 3 jig surface shapes with the same length, namely 7 cm, 1 cm wide. The angle of inclination of the jig includes 15⁰ and 30⁰. The type of flow is laminar conditioned using a volume flow rate of 76.60 liters per second. The jig is conditioned to move up and down using an electric motor. The flow patterns formed were analyzed using visual tests and measurements using Kinovea 0.8.15. The results showed that the shape of the surface of the jig had an effect on the fluid flow pattern. The highest wave occurs at jigs 3 with 15⁰ variation with a wave crest of 4.55 cm, while for jigs 1, 30⁰ variation produces the lowest wave of 1.51 cm. Keywords : Jigs, shape jigs, angle jigs, flow patterns, waves